Transmission loss prediction of reactive silencers using 3-D time-domain CFD approach and plane wave decomposition technique. (November 2016) - Zhu, D.D.; Ji, Z.L.
Abstract: A predictive method is proposed to determine the transmission loss of reactive silencers using the three-dimensional (3-D) time-domain computational fluid dynamics (CFD) approach and the plane wave decomposition technique. Firstly, a steady flow computation is performed with a mass-flow-inlet boundary condition, which provides an initial condition for the following two unsteady flow computations. The first unsteady flow computation is conducted by imposing an impulse (acoustic excitation) superimposed on the constant mass flow at the inlet of the model and then adding the non-reflecting boundary condition (NRBC) when the impulse completely propagates into the silencer. The second unsteady flow computation is conducted for the case without acoustic excitation at the inlet. The time histories of pressure and velocity at the upstream monitoring point as well as history of pressure at the downstream monitoring point are recorded during the two transient computations. The differences between the two unsteady flow computational results are the corresponding acoustic quantities. Therefore, the incident sound pressure signal is obtained by using plane wave decomposition at upstream, while the transmitted sound pressure signal is just the sound pressure at downstream. Finally, those two sound pressure signals in the time-domain are transformed into the frequency-domain by Fast Fourier Transform (FFT) and then the transmission loss (TL) of silencer is determined. For the straight-through perforated tube silencers with and without flow, the numerical results agree well with the published measurements.